Analisis Miskonsepsi Materi Termodinamika Dengan Menggunakan Four Tier Diagnostik Pada Kelas X SMA Negri 1 Sinunukan Tahun Ajaran 2023/2024 - hendra; Eni Sumanti Nasution; Kasmawati (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2024)
This study aims to identify students misconceptionson the concept of thermodynamics by using four-tier diagnostic test with google formulir. This research was condusted at SMA Negeri 1 Sinunukan in the even semester of the 2023/2024 school year. The method used is descriptive method. The subjects of this research were students of class X IPA in SMA Negri 1 Sinunukan who had studied the concept of thermodynamics with a sample of 135 students by selecting samples using apurposive sample technique. The research instrument was a four-tier diagnostic test instrument compiled based on the independent curiculum. The research data was processed based on a combination of student answer on the four- tier diagnostic test. The results showed that overall misconception was 71%,understanding concepts was 15%, and not understanding concepts was 14%.